Comparison between elephant and bovine platelet ultra structure - Rezaian, M; Yamamshiro, S (The Indian Journal of Animal Sciences, 2005)
The present study was performed to elucidate comparisons between bovine and elephant platelets ultra structure. Resting platelets of both animals showed round or discoid shape, and contained many large alpha and glycogen granules and few mitochondria dispersed through the cells. No surface connecting canalicular system (SCCS) was found in the cells of both animals. Though the appearance of the cells in both were round, the cytoskeletons were obviously different. The high amounts of circumferential microtubules assembly in bovine platelet surface were not observed in the elephant cells. Instead, thin filaments aggregation at cortical region of the elephant cells shaped the round appearance of them. The difference may cause more resistance and stability as rings or may limit bovine cells' spreading, not in elephant, and finally, the relation between SCCS formation and the circumferential microtubules is uncertain.